Generation of Widely Tunable Narrow-Linewidth Photonic Microwave Signals Based on an Optoelectronic Oscillator Using an Optically Injected Semiconductor Laser as the Active Tunable Microwave Photonic Filter - Lin, Xiao-Dong; Wu, Zheng-Mao; Deng, Tao; Tang, Xi; Fan, Li; Gao, Zi-Ye; Xia, Guang-Qiong (IEEE photonics journal, 2018)
In this work, a novel optoelectronic oscillator (OEO) structure is proposed for generating widely tunable photonic microwave. In this structure, an optical injection semiconductor laser (OISL) functions as an active tunable microwave photonic filter (MPF). Through controlling the injection power and frequency detuning, the OISL is driven into period-one dynamics whose oscillation frequency can be widely tuned from 10.43 to 65.82 GHz. As a result, the OISL can be regarded as a widely tunable active MPF. By introducing an optical feedback loop, the filtered bandwidth of the widely tunable active MPF can be further reduced. Taking the OISL under optical feedback as a widely tunable narrow-bandwidth MPF and a seeding laser source to establish an OEO structure, widely tunable narrow-linewidth photonic microwave can be generated. The experimental results demonstrate that widely tunable photonic microwaves ranging from 10.43 to 39.10 GHz with linewidths below 0.1 MHz and phase variances below 10 -2 (rad 2 ) can be achieved.